Biomass derived carbon dot decorated ssDNA for a 'turn-on' fluorescent assay for detection of Staphylococcus aureus MNase. (16th March 2021) - Hunsur Ravikumar, Chandan; Nair G., Vishnu; M. P., Raghavendra; Surareungchai, Werasak; Thakur, Archana; Balakrishna, R. Geetha
Abstract : A novel 'turn on' fluorescence aptasensor based on an energy transfer mechanism has been designed using ssDNA conjugated carbon dots (C-dots) and graphene oxide (GO). Abstract : A novel 'turn on' fluorescence aptasensor based on an energy transfer mechanism has been designed using ssDNA conjugated carbon dots (C-dots) and graphene oxide (GO). ssDNA-C-dots on interaction with ssDNA modified GO, allow fluorescence quenching due to energy transfer from the C-dots to GO by DNA duplex bridge formation between them. The property of MNase to cleave DNA is exploited to inhibit the interaction between C-dots and GO. As the bridge breaks, it inhibits interaction and regeneration of fluorescence occurs. Increase in PL intensity is proportional to the concentration of MNase present, thus facilitating the detection of MNase of S. aureus . Different lengths of ssDNA are used to study the mechanism of energy transfer. The C-dots synthesized through a green hydrothermal method using maize biomass are evaluated for cytotoxicity and the measured IC50 value indicates their non-toxicity. The C-dots exhibited 23% fluorescence quantum yield and the sensing mechanism of energy transfer is substantiated by UV visible, PL and time resolved photoluminescence (TRPL) studies. Real time samples were analyzed to validate the probe designed.